SEGURANÇA ALIMENTAR: situação dos serviços de alimentação no Bairro Vila Esperança, São Luís (MA), Brasil - CARVALHO, Eulália Cristina Costa de (2017)
Introduction: Historically, the field of food hygiene was more restricted to aspects such as the presence or absence of a particular contaminant. Today, the discussion surrounding this issue is extended, considering the risks involved in the different stages of production to consumption. This scenario reflects the advances arising with the Brazilian Sanitary Movement, the Industrial Revolution and women entering the labor market and the demand for collective food services and the provision of healthy and safe food with satisfactory hygienic and sanitary conditions. Objectives: To analyze the health profile of food services at the Hope Village neighborhood, Sao Luis - MA; categorize the food services; relate hygienic and sanitary conditions with the risk of food contamination and use of control measures (Good Manufacturing Practices); know the perception of the owners or technicians responsible about their working conditions. Methodology: it is a descriptive quantitative and qualitative, and an epidemiological and cross-sectional survey. Use It will be a checklist of federal health legislation - Ordinance 817/2013 and RDC n ° 216/2004, with interview 10 working in establishments in Hope Village neighborhood, 6 snack bars and 4 restaurants. In the analysis of the data will be used the Epi-info® 7 programs and Excel® 2013.Conclusion: This research aimed to categorization of food services Hope Village neighborhood in São Luís - MA, as allowed to characterize the variation of the sanitary quality of these establishments, among the 10 food service: 8 were categorized in group B (Good sanitary quality) and 2 were eliminated for lack of adequate water supply.